OK/basigin expression on red blood cells varies between blood donors and correlates with binding of recombinant Plasmodium falciparum reticulocyte‐binding protein homolog 5. Issue 8 (29th April 2018) - Ye, Luyi; Zhao, Fengyong; Yang, Qixiu; Zhang, Jiamin; Li, Qin; Wang, Chen; Guo, Zhonghui; Yang, Ying; Zhu, Ziyan
Abstract : BACKGROUND: Recently, basigin (BSG), which carries OK antigens on red blood cells (RBCs), was reported to be the receptor of the Plasmodium falciparum reticulocyte‐binding protein homolog 5 (PfRh5). BSG–PfRh5 is the only essential receptor–ligand pair in P. falciparum invasion that is known to date. However, the kind of OK/BSG polymorphism involved in the selection pressure caused by P. falciparum malaria has not been determined. STUDY DESIGN AND METHODS: Blood samples were collected to detect the expression of OK/BSG. The coding region of PfRh5 was cloned and expressed. Enzyme‐linked immunosorbent assay–based erythrocyte binding assay was used to measure the recombinant PfRh5 (rPfRh5) binding of RBCs with different OK/BSG expressions. Sequencing of the BSG gene and quantification of the BSG mRNA were performed for selected samples. The candidate microRNAs (miRNAs), which might target the BSG gene, were obtained by miRNA sequencing. Dual‐Luciferase reporter assay and overexpression of identified miRNAs were performed in K562 cells. RESULTS: The rPfRh5 was successfully expressed and verified. The OK/BSG expression levels varied among blood donors and were strongly associated with rPfRh5 binding. No single‐nucleotide polymorphism was related to the OK/BSG expression. A potential BSG regulator, miR‐501‐3p, was identified by miRNA sequencing and Dual‐Luciferase assay, but was not proven to regulate the expression of BSG in K562 cells. CONCLUSION: Although the mechanism of OK/BSG expression and regulation on RBCs has not been fully clarified, our findings suggest that the OK/BSG expression levels on RBCs might be related to P. falciparum invasion. Moreover, posttranscriptional regulation might play a role in controlling the OK/BSG expression.